The Urgency of 21st Century Islamic Religious Education Teachers in Social Change (Study of Analysis of Al-Qur'an Hadith) - Ajusman; Kiki Ayu Hermawati; Lia Dwi Utami; Irhas Sabililhaq (al-Afkar, Journal For Islamic Studies, 2024)
Islamic education in the 21st century is known as the era of globalization which is very rapid so that education in the 21st century with the flow of globalization is so rapid that it has big challenges for education, the character of today's students questions the existence of education in Indonesia. The purpose of this study was to analyze the urgency of Islamic Religious Education teachers in the 21st century in social change from the perspective of the Koran and hadith. alim muta'allim and secondary several journals related to the title of the article. The results of Islamic Education research aim to prepare individuals to be successful in the world by using their knowledge and abilities, but also not forgetting the afterlife by carrying out religious teachings by developing good character and then forming human beings who are perfect. The ideal teacher in the 21st century must have the skills needed to create students who have 21st century skills, so the teacher needs to have important competency aspects, namely the character of morality, character of performance and literacy. The urgency of 21st-century Islamic Religious Education teachers in social change from the perspective of the Koran found in surah Al-Imran verse 104 and Al-Luqman verses 18-19 and Hadith, namely instilling character values ​​and becoming an exemplary or exemplary teacher to their students.